2016
DOI: 10.1136/bcr-2015-213046
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic clue for a mid-LAD lesion

Abstract: ECG is still the first diagnostic tool for coronary artery disease. It is possible to predict the localisation of affected vessel(s) through ST and T changes on ECG. Sometimes, reciprocal changes may be the only marker of acute myocardial ischaemia, as single T-wave inversion in lead aVL may represent a coronary artery lesion in the left anterior descending (LAD). A 49-year-old woman presented to the emergency department, with left-sided chest pain. Her initial ECG showed no ischaemic changes. On the third hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…It has been suggested that isolated ST-T changes at V1 and aVL leads are associated with lesions in the left anterior descending artery [2,13].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that isolated ST-T changes at V1 and aVL leads are associated with lesions in the left anterior descending artery [2,13].…”
Section: Discussionmentioning
confidence: 99%